Voies romaines du Rhône à l'Èbre : via Domitia et via Augusta (Documents d'archéologie française, 1997)
Produced following a colloquium held in Perpignan by the Association archéologique des Pyrénées-Orientales, this volume assembles the contributions of 42 researchers of the Languedoc-Roussillon region and adjoining Spanish Catalonia and Aragon. The via Domitia and the via Augusta, two of the most famous roman roads, are treated successively, each section being preceeded by explanatory maps and notices for each of the road stations traversed. The third part examins the structure of these roads and their impact on the organisation of the landscape and discusses the organisation and presentation of conserved sections. A bibliography, general and thematic, as well as a listing comprising the data concerning road itineries concludes this volume, which reviews recent research, an essential work of reference.